LIFT: a feasible option for primary and recurrent fistulas. Issue 6 (2nd November 2021) - Van Hoof, Sander; Van Dessel, Els; Cools, Peter
Abstract: Background: The development of a surgical solution for anal fistulas with minimal recurrence and morbidity remains a challenge. Ligation of the intersphincteric fistula tract (LIFT), however, is a sphincter sparing technique that provides complete resolution of the transsphincteric fistula as well as minimizing recurrence and fecal incontinence. Our goal is to evaluate the efficacy of fistula tract ligation for primary and recurrent fistulas. Methods: A retrospective single-center case study was conducted from data between 2015 and 2019 in a large district hospital in Antwerp, Belgium. Patients who underwent LIFT were included. Demographic patient data as well as primary outcome during the follow-up period were collected. A systematic literature review and analysis was conducted with terms [ANAL FISTULA] [TREATMENT] [LIFT] [LIGATION OF INTERSPHINCTERIC FISTULA]. Primary healing and recurrence associated with surgical modifications were investigated. Results: 4 out of 25 patients presented with early failure (84% primary success rate) after a median follow-up period of 7 months. The median time until recurrence was 105 days. The success rate after a redo ligation was 100%. Twenty-eight studies were included for review and divided into three groups depending on the technical variation of the used technique. The success rate was 74.2% for the LIFT group, 72.9% in the LIFT + group, and 77.5% in the mLIFT group p = .92. Conclusion: LIFT is a feasible treatment option for primary and recurrent fistulas, with excellent success rates where fistula characteristics rather than chosen technique dictate the surgical outcome.